Potensi Aktinomiset Filoplan Asal Tumbuhan Solanaceae sebagai Agens Pengendali Hayati Phytophthora capsici pada Cabai: The Potential of Phyllospheric Actinomycetes from Solanaceae Plants as Biocontrol Agents of Phytophthora capsici on Chili Pepper - Basri, Muhamad; Tondok, Efi Toding; Giyanto (The Indonesian Phytopathological Society (Perhimpunan Fitopatologi Indonesia), 2025)
The Potential of Phyllospheric Actinomycetes from Solanaceae Plants as Biocontrol Agents of Phytophthora capsici on Chili Pepper Chili rot is an important disease caused by an Oomycete species, Phytophthora capsici. This fungus infects chili plants with a potential yield loss of more than 80%. The use of actinomycetes as a biocontrol agent is an environmentally friendly approach that effectively suppresses the growth of P. capsici through the production of antibiotics, lytic enzymes, and competition for space and nutrients. This study aimed to obtain the best actinomycetes isolated from Solanaceae plants that could suppress the growth of P. capsici. This research included isolation of actinomycetes, biosafety assay, antagonistic potential assay, analytic hierarchy process, and molecular identification. There were 71 actinomycetes isolated from 11 plant species in the the Solanaceae family. Actinomycetes isolates that passed the biosafety assay were 39 isolates. The results of antagonistic potential screening revealed 16 actinomycetes isolates capable of suppressing the growth of P. capsici. A dual culture assay showed that actinomycetes isolates were able to inhibit the growth of P. capsici in petri dishes up to 98.2% by isolate 46PPS. Furthermore, in volatile organic compounds assay, the growth of P. capsici was reduced up to 74.1% by isolate 41LAL. While filtrate of actinomycetes isolate 25TPT inhibited growth of P. capsici in liquid medium by up to 98.2%. The cellulolytic index showedthe ability of actinomycetes to break down cellulose molecules, with a cellulase index value of 2.1 by isolate 2LAP. Scoring with the AHP method narrowed down 16 isolates into four best candidates with isolate codes 2LAP, 25TPT, 37LAT, and 41LAL. The results of molecular identification showed that the four selected isolates were Streptomyces pratensis, S. seoulensis, Pseudonocardia tropica, and S. somaliensis.